Philosophical and Methodological Basis of the Property Institute Study - KIZLOVA, Olena S.; HLYNIANA, Kateryna M.; DENYSIAK, Natalia N.; ANDRIIENKO, Valentyna V.; HRYNIAK, Oleh B. (Journal of Advanced Research in Law and Economics, 2019)
The research analyses the main conceptual philosophical and methodological approaches to the comprehension of the property institute as a complex legal institution. The main philosophical and methodological aspects and concepts used in the study of the essence, legal nature and genesis of the property institute in the modern legal field are considered. The issue of the property institute in the context of philosophical analysis, its economic, legal, subjective and objective features and conceptual content are investigated. It is necessary to apply the main philosophical and methodological concepts while analyzing and studying of law in and of itself and the property institute in particular. This assertion is based on the fact that the relevance of philosophical comprehension of the law phenomenon as a whole, and certain legal phenomena in particular, is associated with both practical issues of the society’s development, and theoretical issues, directly related to the ideological and methodological support of law. It is established, that the fundamentality of the issue being solved in science is determined by the required degree of awareness of the integrity of scientific significance. Philosophical approach as a holistic form of methodological analysis can become a means of such awareness.